2014
DOI: 10.1038/ki.2013.328
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a urine metabolomic signature in patients with advanced-stage chronic kidney disease

Abstract: The prevalence of chronic kidney disease (CKD) is increasing and frequently progresses to end-stage renal disease. There is an urgent demand to discover novel markers of disease that allow monitoring disease progression and, eventually, response to treatment. To identify such markers, and as a proof of principle, we determined if a metabolite signature corresponding to CKD can be found in urine. In the discovery stage, we analyzed the urine metabolome by NMR of 15 patients with CKD and compared that with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
82
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(95 citation statements)
references
References 22 publications
12
82
1
Order By: Relevance
“…Serum metabonomics indicated that specific metabolic disturbances precede β-cell autoimmunity in humans and can be used to identify T1D children [80]. These findings suggest alternative metabolism-related pathways as therapeutic targets to prevent diabetes.…”
Section: Metabolic Diseases Type 1 Diabetic (T1d)mentioning
confidence: 90%
“…Serum metabonomics indicated that specific metabolic disturbances precede β-cell autoimmunity in humans and can be used to identify T1D children [80]. These findings suggest alternative metabolism-related pathways as therapeutic targets to prevent diabetes.…”
Section: Metabolic Diseases Type 1 Diabetic (T1d)mentioning
confidence: 90%
“…Changes in the levels of metabolites, such as asymmetric dimethyl arginine 255 or long-chain acylcarnitine 256 , that contribute to complications in CKD and are involved in cardiovascular complications in patients undergoing dialy sis 169,256 can be reliably measured and are providing new insights into the pathogenesis of complications associated with uraemia [255][256][257] . Studies at the metagenomic level, that is on genetic material from bacterial communities such as the gut microbiota, provide insights into the effects of CKD on the microbiome and, conversely, on the effects of changes in the microbiome on the mani festations of CKD.…”
Section: Metabolomics and Metagenomicsmentioning
confidence: 99%
“…In this regard, the process has started with the application of systems biology tools to simple sets of samples (which can be obtained from plasma, urine, faeces or circulating leukocytes). For example, one study performed metabo lomics analyses in a group of 41 patients with stage 3-4 CKD 255 , whereas another analysed metabolic signatures in urine samples of a small series of 13 patients with stage 4-5 CKD 257 .…”
Section: Integration Of Omic Sciencesmentioning
confidence: 99%
“…As discussed below, the use of spironolactone represents a modality of dual RAAS blockade. Proteomics of urinary exosomes or urinary metabolomics may also provide molecular signatures for patient stratification [Benito-Martin et al 2013;Zubiri et al 2013;Posada-Ayala et al 2014].…”
Section: Can the Safety Record Of Dual Ras Blockade Be Improved?mentioning
confidence: 99%